Ethnobotanical study of wild edible plants in the mountainous regions of Semnan Province, Iran - Majid Jalali; Mehdi Abedi; Farshid Memariani; Abdolbaset Ghorbani (BMC, 2024)
Abstract In mountainous areas, wild edible plants are an important part of the local diet. Climate change and anthropogenic activities have profound effects on wild edible plants in these areas. Ethnobotanical studies are important for understanding the use patterns and harvest impacts on these plants. In this regard, the Shahrood region, with its diverse historical/ethnic background, is an appropriate starting point to investigate exploitation patterns and impacts of harvest of wild edible plants. During 2021-2022, ethnobotanical surveys were conducted in 12 villages in the region using semi-structured interviews and participatory observations. Data collection included assessing wild edible plant species diversity, their habitats, collection time and quantities, plant parts used and methods of consumption and preparation. The data were analyzed using use report indicators, relative frequency of citations, and use value (UV). A total of 1086 use reports were documented from a total of 44 interviews. A total of 67 wild species (66 plants and 1 fungus) belonging to 54 genera and 24 families were used as edible in the study area. Rosaceae (9 species), Apiaceae (8), Lamiaceae (8), Asteraceae (7), and Amaryllidaceae (5) were the families with the most reported species. Allium (5 species) was the most diverse genus in terms of species diversity. Herbs were the most commonly used life form (79.1%), followed by shrubs (13.4%) and trees (6%). The most consumed plant parts were young leaves (25%) and young aerial parts (21.4%). There were 13 use categories identified. The majority of edible plants were collected in April-May, mainly from areas nearby villages (37.7%) and rangelands (33.7%). The most important edible plants in the study area were Allium iranicum (Wendelbo) Wendelbo (UV = 1.7), Mentha longifolia (L.) Huds. (1.5), Allium umbilicatum Boiss. (1.47), Tragopogon graminifolius DC. (1.38), Lepidium draba L. (1.27), Urtica dioica L. (1.18), Falcaria vulgaris Bernh. (1.13), Malva neglecta Wallr. (1.11) and Eremurus sp. (1.09). Our results showed diverse and valuable knowledge for wild edible plants in this region, which should be considered in the conservation and management plans in the region.